2008
DOI: 10.1007/s10681-008-9812-4
|View full text |Cite
|
Sign up to set email alerts
|

Allelic variation and genetic diversity of high molecular weight glutenin subunit in Chinese endemic wheats (Triticum aestivum L.)

Abstract: The high molecular weight glutenin subunit (HMW-GS) compositions of 66 Chinese endemic wheats were determined by sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE). Ten alleles at the Glu-1 loci were detected in 50 Tibetan weedrace wheat accessions which in combination resulted in seven different HMW-GS patterns. Four HMW-GS patterns were observed among 10 Yunnan hulled wheat accessions, and two patterns in six Xingjiang rice wheat accessions. Two novel alleles (Bx7** ? By8, Bx7 ? By8**) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 13 publications
3
13
0
Order By: Relevance
“…Subunit 1 at Glu-A1, subunits 7+8, 7+9, 6+8, 13+19, 17+18, 6+22 and the new allele at Glu-B1 and subunits 3+12 and 2+11 at Glu-D1 appeared less frequently in this study while subunits 20 and 7 at Glu-B1 were observed more frequently. A total of 16 alleles encoding for HMW-GS were present in only 40 cultivars of Saharan bread wheat and this high level of diversity agrees with the results of Fang et al (2009) and with the results of Wei et al (2001). Major differences between Saharan wheats and other collections were observed in the frequency of subunit 7 although Saharan wheats had subunit pair 6+22 (4 varieties) controlled by Glu-B1o.…”
Section: Saharan Bread Wheatssupporting
confidence: 90%
See 1 more Smart Citation
“…Subunit 1 at Glu-A1, subunits 7+8, 7+9, 6+8, 13+19, 17+18, 6+22 and the new allele at Glu-B1 and subunits 3+12 and 2+11 at Glu-D1 appeared less frequently in this study while subunits 20 and 7 at Glu-B1 were observed more frequently. A total of 16 alleles encoding for HMW-GS were present in only 40 cultivars of Saharan bread wheat and this high level of diversity agrees with the results of Fang et al (2009) and with the results of Wei et al (2001). Major differences between Saharan wheats and other collections were observed in the frequency of subunit 7 although Saharan wheats had subunit pair 6+22 (4 varieties) controlled by Glu-B1o.…”
Section: Saharan Bread Wheatssupporting
confidence: 90%
“…This new subunit, designated new3, was present in the cultivar Fritas. Tahir et al (1996) reported subunit 7f in bread wheat landraces from Pakistan and Fang et al (2009) identified subunit 7** in Chinese endemic wheats with faster mobility than subunit 7. However, without making a direct comparison, it is not possible to decide whether subunit 7 detected in the study is identical or not to subunit 7f or 7**.…”
Section: Allelic Diversity Of Glutenins In Saharan Wheatsmentioning
confidence: 99%
“…These Chinese landraces are of potential importance as sources of novel genes for transfer to released varieties. Provided the significance of HMW-GS in the role of flour quality, several novel glutenin subunits such as 1Bx7*, 1By8*, 1By8** (Liu et al 2007) and Bx7** (Fang et al 2009) and 1Dx2.6 (Cong et al 2007) have been detected in the Chinese wheat landraces. In the work reported in this paper, two novel HMW-GS The Aegilops tauschii (DtDt) is considered to be the D-genome donor of the common wheat (Kihara 1944;McFadden and Sears 1946;Riley 1965).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of HMW-GS on baking quality mainly depends on the composition of the HMW-GS and the quantity of each subunit (Sontag-Strohm et al 1996;Ragupathy et al 2008;Jin et al 2012). The results of these HMW-GS studies were widely used in wheat quality breeding for determining which parents to cross and for selection of progeny (Redaelli et al 1997;Fang et al 2009;Rasheed et al 2012). The structure of LMW-GS is similar to that of HMW-GS, and the composition of these molecules is also strongly related to wheat baking quality (Payne 1987;Gupta and Shepherd 1990;Sontag-Strohm et al 1996;Redaelli et al 1997;Gianibelli et al 2001).…”
Section: Introductionmentioning
confidence: 99%